The Effect of Service Quality on Customer Satisfaction at Saripul Motorcycle Workshop, Lesung Batu Village, Pagar Gunung District, Lahat Regency - Soleh, M.; Dewi, Dismita Citra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
In this study, we want to learn how service quality affects consumer satisfaction with Saripul motor boats in the Lesung Batu, Pagar Gunung District, Lahat Regency, and what factors could influence consumer satisfaction with Saripul motor boats. This research methodology includes questionnaires, observational methods, documentation, surveys, and studies of participation using likert scales. A total of 82 consumers were surveyed using proportional stratified random sampling as the sampling technique. This study used a quantitative approach, which is to say, it used instrument reliability and validity tests, classical assumption tests like heteroskedasticity and normalcy, hypothesis tests like parcial (uji-t), F, determination (R2), linear regression, and a correlation technique. The research results show that: in the combined regression model Y = 1,192 + 0.754X, there is a positive and significant relationship between service quality and consumer satisfaction with the Saripul motor boat from Lesung Batu Village, Pagar Gunung District, Lahat Regency. We know that the service quality influences customer satisfaction since the calculated F-value of 1503,942 > the tabled F-value of 3.96 or a P-value of 0,00 < 0.05. In contrast, the t-test result of product quality 38,781 > ttable = 1,664 indicates that the service quality variable has a positive effect on the dependent variable, consumer satisfaction.